2023
DOI: 10.1371/journal.pone.0277994
|View full text |Cite
|
Sign up to set email alerts
|

Physical inactivity among corporate bank workers in Accra, Ghana: Implications for health promotion

Abstract: Introduction Any type of activity that results in caloric expenditure has the potential to reduce the risk of cardiovascular diseases; nonetheless, most people, especially office workers, are physically inactive. This study sought to evaluate the extent of physical inactivity and its determinants among the staff of selected banks in Accra, Ghana. Methods This was a cross-sectional study involving 219 banking staff randomly selected from five commercial banking institutions in Accra, Ghana. Demographic data w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The general sedentary time among bank employees (42.5 h/w or 364 m/day) is less than what was found in a comparable study (552 m/day) involving German adults [69]. However, sedentary behavior appears to be common among bank employees, with findings from two distinct investigations showing a prevalence of physical inactivity at 60% [70] and 82% [71]. While several intrinsic and extrinsic factors may contribute to sedentary behavior, findings from a study examining barriers to adopting healthier lifestyle habits underline that the extent of time allocated for physical exercise is a pivotal factor driving the rising prevalence of physical inactivity [72].…”
Section: Discussionmentioning
confidence: 57%
“…The general sedentary time among bank employees (42.5 h/w or 364 m/day) is less than what was found in a comparable study (552 m/day) involving German adults [69]. However, sedentary behavior appears to be common among bank employees, with findings from two distinct investigations showing a prevalence of physical inactivity at 60% [70] and 82% [71]. While several intrinsic and extrinsic factors may contribute to sedentary behavior, findings from a study examining barriers to adopting healthier lifestyle habits underline that the extent of time allocated for physical exercise is a pivotal factor driving the rising prevalence of physical inactivity [72].…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, the German study also found that sedentary time was higher in males than in females [ 67 ], whereas in contrast, the present study observed no gender difference in sedentary time. Two separate studies examining bank employees in Nigeria and Ghana reported a prevalence of physical inactivity of 60% and 82%, respectively [ 68 , 69 ]. In this regard, a general trend of higher physical inactivity prevalence in females compared to males has also been reported [ 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two separate studies examining bank employees in Nigeria and Ghana reported a prevalence of physical inactivity of 60% and 82%, respectively [ 68 , 69 ]. In this regard, a general trend of higher physical inactivity prevalence in females compared to males has also been reported [ 69 , 70 , 71 ]. An investigation on barriers to adopting healthy behaviors highlighted inadequate time for exercise as a major reason for the recent high levels of physical inactivity [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the present study found no significant age-based difference in sedentary time, it is worth noting that middle-aged participants showed a tendency toward having less sedentary time (38.8 h per week) compared to both their younger (43.9 h per week) and older (45.3 h per week) colleagues. According to the results from two different investigations, the prevalence of physical inactivity among bank employees was documented as 60% [ 75 ] and 82% [ 76 ], without any significant difference between younger and older adults [ 76 ]. However, one study has reported that younger adults (aged 30–49 years) exhibited higher levels of physical inactivity compared to their older counterparts (those aged 50–69 years) [ 77 ].…”
Section: Discussionmentioning
confidence: 99%